Nanotoxicity of nanodiamond in two and three dimensional liver models. (2017) - Khanal, D.; Hau, H.; Kondyurin, A.; Fu, D.; Ramzan, I.; Chrzanowski, W.
Among classes of nanoparticles developed as drug carriers and theranostics, nanodiamond (ND) has been gaining an increasing attention owing to its biocompatibility, easy functionalisation and chemical stability. Although biocompatibility studies on nanodiamond produced by detonation technique have been explored extensively, NDs produced by laser assisted technique are yet to be investigated. Here, we present comparative study on toxicity of NDs in 2D and 3D liver models. Results suggest toxicity occurs on the 2D model at higher concentrations of NDs after long term exposure. However, cytotoxic effect was not observed in the case of the 3D model. In addition, alterations in nanomechanical properties of the cells after uptake of NDs were detected by a Lorentz contact resonance (LCR) spectroscopic study. Overall, the results indicate differences in the toxicity profile of NDs in 2D and 3D and long term toxicity studies on NDs produced by laser assisted technique must be done prior to any biomedical applications.